Perspektif digital marketing communication dalam memasarkan skincare di indonesia - Hapsara, Osrita; Casmudi, Casmudi; Sjuchro, Dian Wardiana; Murtono, Taufik; Asfar, Dedy Ari (Jurnal Komunikasi Profesional, 2021)
The rapid development of skin care products (Skincare) through social media has changed the paradigm of the digital marketing model in general. This article discusses digital marketing models that skin care products use in marketing their products. The method used was Krippendorff content analysis which was carried out through digital observation on the Instagram account of skin care products (Skincare) Elvicto @ elvicto.id from March 1, 2021 to March 31, 2021. The results of this study indicate that Elvicto is more engaged in a digital marketing communication strategy through marketing. Instagram @ elvicto.id which is dominated by personal selling strategies.